2014
DOI: 10.1111/jir.12151
|View full text |Cite
|
Sign up to set email alerts
|

A tale worth telling: the impact of the diagnosis experience on disclosure of genetic disorders

Abstract: Background Research suggests children with genetic disorders exhibit greater coping skills when they are aware of their condition and its heritability. While the experiences parents have at diagnosis may influence their decision to disclose the diagnosis to their children, there is little research into this communication. The aim of the current study was to examine the relationship between the diagnosis experience and the disclosure experience for parents of children with intellectual disabilities; with a chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…Information support is consistently identified as a significant factor impacting parents' experiences of caring for their child with an intellectual disability (Willingham-Storr 2014). While recommendations suggest a need to provide substantial amounts of information to parents at the time of receiving a diagnosis of disability (Skotko et al 2009, Sheets et al 2011, the literature consistently reports that health professionals fail to provide enough current, comprehensive, accurate, balanced information about a child's condition and its implications for the child and family when informing parents of their child's diagnosis (Skotko 2005, Skotko & Bedia 2005, Gammons et al 2010, Choi et al 2011, Phelps et al 2012, Sheets et al 2012, Nelson Goff et al 2013, Willingham-Storr 2014, Goodwin et al 2015, Marshall et al 2015. Many parents therefore turn to peer support networks to assist them to understand their child's condition.…”
Section: Introductionmentioning
confidence: 99%
“…Information support is consistently identified as a significant factor impacting parents' experiences of caring for their child with an intellectual disability (Willingham-Storr 2014). While recommendations suggest a need to provide substantial amounts of information to parents at the time of receiving a diagnosis of disability (Skotko et al 2009, Sheets et al 2011, the literature consistently reports that health professionals fail to provide enough current, comprehensive, accurate, balanced information about a child's condition and its implications for the child and family when informing parents of their child's diagnosis (Skotko 2005, Skotko & Bedia 2005, Gammons et al 2010, Choi et al 2011, Phelps et al 2012, Sheets et al 2012, Nelson Goff et al 2013, Willingham-Storr 2014, Goodwin et al 2015, Marshall et al 2015. Many parents therefore turn to peer support networks to assist them to understand their child's condition.…”
Section: Introductionmentioning
confidence: 99%
“…27 Inadequate access to information is associated with increased stress and uncertainty for parents and negatively influences their engagement with services, potentially denying them the advantages of a precise diagnosis. 28 Our survey did not gather sufficient demographic data to determine whether hard-pressed families were less likely to seek online content.…”
Section: Discussionmentioning
confidence: 99%
“…A number of parents also stated that they had had questions on the hereditability of the disease. The diagnosis of a hereditable dis- ease can be difficult to cope with [6,17,18]. Parents can experience feelings of guilt for having transmitted the disease [9,11,13].…”
Section: Remaining Questions After the Initial Medical Consultationmentioning
confidence: 99%
“…However, data on how parents experience the reveal of their child's diagnosis is scarce. Studies on disclosure of genetic disorders underlying intellectual disability have shown that most parents find the diagnosis experience difficult [6,17]. Parents wish for a private setting and accurate and up-todate information [18].…”
Section: Introductionmentioning
confidence: 99%